Salmonella enterica serovar Enteritidis biofilm lifestyle induces lower pathogenicity and reducesinflammatory response in a murine model compared to planktonic bacteria - Giacomodonato, Mónica Nancy (2021)
Salmonella enterica serovar Enteritidis (S. Enteritidis) is the most frequent serovar involved in human salmonellosis. It has been demonstrated that about 80% of infections are related to biofilm formation. There is scant information about the pathogenicity of S. Enteritidis and its relationship to biofilm production. In this regard, this study aimed to investigate the differential host response induced by S. Enteritidis biofilm and planktonic lifestyle. To this purpose, biofilm and planktonic bacteria were inoculated to BALB/c mice and epithelial cell culture. Survival studies revealed that biofilm is less virulent than planktonic cells. Reduced signs of intestinal inflammation and lower bacterial translocation were observed in animals inoculated with Salmonella biofilm compared to the planktonic group. Results showed that Salmonella biofilm was impaired for invasion of non-phagocytic cells and induces a lower inflammatory response in vivo and in vitro compared to that of planktonic bacteria. Taken together, the outcome of Salmonella–host interaction varies depending on the bacterial lifestyle.